IMAGING DIAGNOSIS—MAGNETIC RESONANCE IMAGING FEATURES OF A MULTIFOCAL OLIGODENDROGLIOMA IN THE SPINAL CORD AND BRAIN OF A DOG. Issue 5 (4th August 2016) - Schkeeper, Amy E.; Moon, Rachel; Shrader, Stephanie; Koehler, Jey W.; Linden, Daniel; Taylor, Amanda R.
Abstract: An 8‐year‐old neutered male Toy Poodle was presented with chronic, progressive tetraparesis, and possible seizures. Magnetic resonance images demonstrated an extensive, T1 and T2 hyperintense contrast enhancing mass in the cervical spinal cord. Three nodules were present on the surface of the thalamus, with enhancement most evident on delayed images. A diagnosis of high‐grade oligodendroglioma was confirmed with postmortem histopathology and immunohistochemical labeling. Oligodendroglioma should be considered as a differential for T1 hyperintense intraaxial or intramedullary lesions with contrast enhancement. If enhancement is not visualized on postcontrast images, delayed images may be beneficial.